The Effectiveness of the Alphabet Hopscotch Game in Improving Letter Recognition Skills in Children Aged 5-6 Years - Puti Juliani; Elise Muryanti (Universitas Sebelas Maret, 2026)
Early childhood children face various difficulties in letter recognition, such as understanding letter shapes, writing their names, pronouncing letter combinations, and recognizing written words related to objects in their surroundings. One enjoyable approach for children in learning is through play-based activities. This study aimed to determine the effectiveness of the alphabet hopscotch game in improving children’s letter recognition skills. The research employed a quantitative method with quasi-experimental design. The population consisted of children in class B2 (experimental group) and class B3 (control group), with a sample of 15 children. Data were collected using a test instrument. The data analysis techniques included normality testing, hypothesis testing, and effect size analysis using SPSS version 26. The results showed that the mean score of the experimental class was 20.80, while the control class obtained a mean score of 19.40. Based on the t-test results, the significance value was 0.916 < 0.05, and the effect size value was 1.17, which was categorized as strong. Therefore, it can be concluded that the alphabet hopscotch game is effective in improving letter recognition skills in children aged 5-6 years.